2022
DOI: 10.1101/2022.01.10.475704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spinal cord homeostatic plasticity gates mechanical allodynia in chronic pain

Abstract: Central sensitization caused by disinhibition of spinal cord circuits is a key mechanism of mechanical allodynia in neuropathic pain. Despite intense efforts, the molecular mechanisms that drive disinhibition and induce allodynia after peripheral nerve injury remain unclear. Using the spared-nerve injury (SNI) model of allodynia, we here demonstrate that SNI induces disinhibition of spinal nociceptive circuits by triggering homeostatic synaptic plasticity. Specifically, SNI-triggered homeostatic plasticity sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The efficacy of their synaptic connection with their targets could be reduced, through pruning of their terminals, decreased vesicular content of their inhibitory transmitters, or decreased post-synaptic receptors. This hypothesis is supported by a recent study demonstrating that PV neurons lose their inhibitory effect on postsynaptic targets after nerve injury (Cao, Scherrer & Chen, 2022). The mechanisms that cause this reduced inhibition remain unclear.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The efficacy of their synaptic connection with their targets could be reduced, through pruning of their terminals, decreased vesicular content of their inhibitory transmitters, or decreased post-synaptic receptors. This hypothesis is supported by a recent study demonstrating that PV neurons lose their inhibitory effect on postsynaptic targets after nerve injury (Cao, Scherrer & Chen, 2022). The mechanisms that cause this reduced inhibition remain unclear.…”
Section: Discussionmentioning
confidence: 72%
“…Importantly, nearly 80% of WGA-IR neurons were not labeled by PKCg, indicating that PV neurons may have several other targets in the dorsal horn, including the recently reported vertical cells (Boyle et al, 2019). It was recently reported that the inhibitory output of PV neurons onto PKCg neurons was significantly lower in nerve injured mice (Chen, Scherrer & Cao, 2022), further supporting the notion of a disinhibition of postsynaptic targets. In these excitatory neurons, activity of the PKCγ enzyme was shown to be central to their role in mechanical allodynia (Malmberg et al, 1989;Miraucourt, Dallel & Voisin 2007;Petitjean et al, 2015).…”
Section: The Allodynic Effect Of Decreasing Pvp Expression Is Allevia...mentioning
confidence: 81%
See 3 more Smart Citations